2011
DOI: 10.1002/adfm.201001602
|View full text |Cite
|
Sign up to set email alerts
|

Open‐Ended, N‐Doped Carbon Nanotube–Graphene Hybrid Nanostructures as High‐Performance Catalyst Support

Abstract: A hierarchical N-doped carbon nanotube-graphene hybrid nanostructure (NCNT-GHN), in which the graphene layers distributed inside the CNT inner cavities, is designed to support noble metal (e.g. PtRu) nanoparticles efficiently. Well-dispersed PtRu nanoparticles with diameters of 2-4 nm are immobilized onto NCNT-GHN supports by a low-temperature chemical reduction method without requiring any pretreatment. Compared with conventional CNTs and commercial catalyst, much enhanced catalytic performance is achieved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
193
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(201 citation statements)
references
References 53 publications
1
193
0
Order By: Relevance
“…[1,2] The extraordinary properties of this intriguing material have been used to provide advantage in numerous areas including composites, energy storage and conversion, nanoelectronics, sensors, biosensors, as a support for catalysts and transparent conducting films. [1,[3][4][5][6][7][8][9] However, in all of these studies, the performance levels obtained are limited by the ability to translate the properties inherent in graphene nanocomponents into the macroscopic structures needed for practical applications. [4] In this context, the recent discovery of liquid crystalline (LC) behavior of graphene oxide (GO) dispersions in various organic, [8] and aqueous media brings added control to the assembly of larger structures using the chemical process approach.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The extraordinary properties of this intriguing material have been used to provide advantage in numerous areas including composites, energy storage and conversion, nanoelectronics, sensors, biosensors, as a support for catalysts and transparent conducting films. [1,[3][4][5][6][7][8][9] However, in all of these studies, the performance levels obtained are limited by the ability to translate the properties inherent in graphene nanocomponents into the macroscopic structures needed for practical applications. [4] In this context, the recent discovery of liquid crystalline (LC) behavior of graphene oxide (GO) dispersions in various organic, [8] and aqueous media brings added control to the assembly of larger structures using the chemical process approach.…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, fullerene-graphene hybrids have been experimentally produced and theoretically investigated [34][35][36][37][38][39]. In particular, nanotube-graphene hybrid also has great potential application [40][41][42][43][44][45][46][47][48]. Theoretical work suggested that a covalently bonded graphene-nanotube hybrid material would extend those properties to three dimensions, and be useful in energy storage and nanoelectronic technologies [40].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the improvement of ferroelectric property and layer resistivity, N and B doping is widely adopted in thin films studies [31][32][33][34]. In this section, we consider the hybrid structure with both existences of N-and B-dopants.…”
Section: Hybrid Structures With N-and B-dopantmentioning
confidence: 99%
“…The N-doped graphene is also reported by Wang et al [30] as a good candidate for the application as electrocatalyst fuel cell, field-effect transistor and lithium batteries. Specifically, the Ndoped nanotube-graphene hybrid structure has been envisioned with promising applications in the field of catalysis, gas storage and energy storage [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation